Pengolahan Motif Batik Perpaduan Unsur Tradisi Jawa dan Jepang - Morinta Rosandini; Imam Syafrudin (JURNAL RUPA, 2017)
PPI Ishikawa as one of the Indonesian student community in Japan invited Batik practitioners to design Batik motif, that not only has elements of traditional culture but also represents the character of that community. The purposes were to rise a pride of that community and to introduce Batik as Indonesian culture to local residents as well. Therefore, to fulfill those purposes, it is needed a research in designing Batik motifs that combine traditional Javanese ornaments as the original character of Batik and Japanese elements as a culture that developed around the community. The purpose of this research was to create ornaments pattern composition applied to Batik technique. The research method used was by conducting qualitative methods, including a literature study for data collection, an exploratory study of the elements of Javanese and Japanese culture, and an experiment on Batik Tulis technique. The result of this research was Batik cloth sheet with ‘Truntum’ motif as a character of Javanese Batik, combined with the statute of cherry blossom, pagoda, and heron motifs as a character of Japan.